Essence and legal nature of restriction of rights owner's rights in the system of copyright and related rights - Viyvanko, Oleh (Actual problems of law (Aktual'ni problemi pravoznavstva), 2022)
Legal protection of intellectual property is based on exclusive rights, which allow the subject to exercise in respect of a particular object of authority to own, use and dispose of it. According to Art. 418 of the Civil Code of Ukraine, such a right is inviolable, because no one can be deprived of it or restricted in its exercise, except in cases clearly defined by law. These restrictions are usually imposed in the public or state interest. Thus, the legislation of Ukraine allows for the restriction of rights in emergency situations (epidemic, catastrophe, natural disaster, etc.). Under these conditions, their use is allowed without the permission of the copyright holder, but with the mandatory payment of compensation. Thus, subjective rights are usually limited to the benefit of state, public and public interests.Any restrictions, termination, revocation of subjective rights are applied solely by law. Most often, such restrictions apply to property rights to intellectual property rights. These limitations are significant.The monopoly of the right holder provides an opportunity to prohibit the use of objects to which the rights belong to him. However, in order to establish a balance between its interests and the interests of society, the state law allows the restriction of rights to intellectual property, which do not create significant obstacles to the realization of property rights and the legitimate interests of intellectual property rights.The limit of law is all the possibilities that a person is able to acquire for himself in connection with the legal definition of his natural rights. Restriction of the right is, as a rule, actions of the third party which are directed on impossibility of realization by the subject of the rights in full.The purpose of the article is to define the concept and essence of restriction of rights, their role in the exercise of intellectual property rights.